Positron Emission Computed Tomography Imaging of Synaptic Vesicle Glycoprotein 2A in Alzheimer’s Disease - Kong, Yanyan; Zhang, Shibo; Huang, Lin; Zhang, Chencheng; Xie, Fang; Zhang, Zhengwei; Huang, Qi; Jiang, Donglang; Li, Junpeng; Zhou, Weiyan; Hua, Tao; Sun, Bomin; et al. (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder seen in age-dependent dementia. There is currently no effective treatment for AD, which may be attributed in part to lack of a clear underlying mechanism. Early diagnosis of AD is of great significance to control the development of the disease. Synaptic loss is an important pathology in the early stage of AD, therefore the measurement of synaptic density using molecular imaging technology may be an effective way to early diagnosis of AD. Synaptic vesicle glycoprotein 2A (SV2A) is located in the presynaptic vesicle membrane of virtually all synapses. SV2A Positron Emission Computed Tomography (PET) could provide a way to measure synaptic density quantitatively in living humans and to track changes in synaptic density in AD. In view of the fact that synaptic loss is the pathology of both epilepsy and AD, this review summarizes the potential role of SV2A in the pathogenesis of AD, and suggests that SV2A should be used as an important target molecule of PET imaging agent for the early diagnosis of AD.